An Approximation Between Theory of Fundamental Rights and Behavior Analysis - Versoza-Carvalhal, Cassiana Sterza; Carrara, Kester [UNESP] (My University, 2024)
The Theory of Fundamental Rights and the Skinnerian Ethical System have quite different historical and theoretical origins, on the other hand, they have objectives that are similar: to plan deliberate interventions, guided by a set of values, with the purpose of producing certain consequences in society. The objective of this work is to demonstrate that these two fields of knowledge have a contextualist approach to values and that this contextualist view would be a starting point for the dialogue between them. This dialogue could enhance the discussions and scope of both areas and produce advances toward your goals. Fundamental rights had their origin in a natural law doctrine, in which there is the idea that natural rights exist, even if they are not expressed in legal norms. However, legal positivism doctrines of fundamental rights prevail today, which assume that only the norms that appear in the legal system are a right. It is the legal positivism doctrine that allows a contextualist analysis of fundamental rights because it conceives them as results of a dynamic and complex process of collective struggles and achievements that come to be endorsed by the social and state order. In the Skinnerian Ethical System, values are understood as reinforcing consequences selected throughout the history of the species, individual and culture, and usually are different between individuals and societies, depending on the history of each one. Just like all behavioral phenomenon values arise from the interaction between organism and environment so that for Radical Behaviorism there are no absolute values in relation to what is ethical or unethical, since these criteria arise from contingencies. The Theory of Fundamental Rights and the Skinnerian Ethical System defend different set of values, even though there may be similarities. However, in both cases, the values are understood as the result of social relations and historical events from a specific time. It means that the defense of certain values by a social group is always a result of concrete relationships based on a specific social context. The historical dimension of values leads to the flexible and open character of the set of values defended in either case, so, in both cases, their contents can suffer additions and alterations and are subject to social transformations. These points in common open up possibilities for dialogue between these fields of knowledge that can be very fruitful for achieving the objectives they propose. Futhermore, highlight the delicate problem of understanding values as historically determined and still taking them as guides for cultural planning, in the Skinnerian Ethical System, and public policies, in the Theory of Fundamental Rights.
Uma Aproximação Entre Teoria dos Direitos Fundamentais e Análise do Comportamento
Keywords: behavior analysis; contextualism; public policies; skinnerian ethical system; theory of fundamental rights; values